Automatic Transfer Switch Kontrol Menggunakan Internet Of Thing (IoT) - RAHMAN, M. FADHILUR (Fakultas Teknik, Universitas Wiraraja, 2023)
This research aims to develop and implement an Automatic Transfer Switch (ATS) control system using the Internet of Things (IoT) within the Nurul Jadid University environment. ATS is an important device in an electrical distribution system that allows automation of switching between primary and backup electrical power sources in fault situations. By utilizing IoT technology, this research aims to improve the efficiency, performance and monitoring of ATS at Nurul Jadid University, The research methodology involves designing, manufacturing, and testing a prototype of an IoT-based ATS system. Smart sensors will be installed on ATS devices to monitor parameters such as voltage, current, temperature and device status. Data collected by sensors will be sent via the IoT network to a monitoring platform that can be accessed in real-time by operators and maintenance personnel. It is hoped that the results of this research will increase the availability and reliability of electricity supply at Nurul Jadid University, by enabling early detection and quick action in disturbance situations. In addition, this system will also help optimize the use of electrical resources and reduce unnecessary energy consumption. By combining IoT technology with ATS control, this research presents an innovative solution to increase the efficiency and reliability of electricity supply in university environments. The results of this research can be a guide for other institutions interested in adopting similar technology in their electricity resource management